A novel method to improve sow reproductive performance: Combination of pre-weaning immunization against inhibin and post-insemination hCG treatment - Ri-hong GUO; Pei-yuan HE; Yan-long MAI; Zi-cun DAI; Fang CHEN; Zhen-dan SHI (Journal of Integrative Agriculture, 2020)
The feasibility of a novel method to improve sow reproductive performance by combining inhibin immunization and hCG treatment was tested using in vivo and in vitro experiments. In the in vivo experiment, 106 sows were administered an inhibin immunogen on day 7 prior to weaning, and 56 non-treated sows served as the controls. Sows exhibiting oestrous behaviour on day 5 after weaning were artificially inseminated. On day 5 post-insemination, a subset of 50 inhibin-immunized sows received an injection of 1 000 IU human chorionic gonadotropin (hCG). Our results showed that pre-weaning immunization against inhibin marginally improved (P=0.068) total litter size and significantly increased (P=0.044) the live litter size. The overall differences in farrowing rates and live litter size tended toward significance (P=0.10) in the three groups, and the differences in total litter size were not significant (P=0.18). In the in vitro experiment, activin and hCG dose-dependently suppressed (P<0.001) and stimulated (P<0.001) progesterone (P4) secretion in cultured pig granulosa cells (GCs), respectively, and the suppression effect of activin was reversed (P<0.001) by hCG. Activin suppressed P4 secretion mainly by downregulating (P<0.001) the expression of StAR, Cyp11a1, and 3β-HSDII, whereas hCG prevented (P<0.001) the suppression effects. These results indicate that the combination of pre-weaning immunization against inhibin and post-insemination hCG treatment provides a novel method for improving sow reproductive performance.